Evaluation of Brahman-crossed Boran, pure Brahman, and pure Boran cattle kept at Abernossa ranch of the Ministry of Agriculture - Gebre-Wold, A.; Bekele, T.; Worku, G.; Gebre-Meskel, T.; Ketema, E. (1989)
Reproductive and growth performances of purebred Brahman and Boran cows and their crossbred calves were investigated at Abernossa ranch in Ethiopia. The calves performances were evaluated in relation to growth from birth to weaning including birth weight, growth rate, to weaning weight.